FACTORS INFLUENCING INDONESIAN MARRIED FEMALE STUDENTS PURSUING A HIGHER EDUCATION DEGREE OVERSEAS - Irnie Victorynie; Ismail Sheikh Ahmad; Riski Munandar Hutapea; Saddam Husein (LPMPP Universitas Negeri Yogyakarta, 2021)
Married female students face different learning experiences in higher education compared to unmarried female students. This research was conducted to determine the experiences of Indonesian married female students. The aims of this study are to identify the various factors which encourage Indonesian married female students to continue their studies, to examine the obstacles that they experience during their studies, and to identify the efforts to overcome the obstacles which are faced by the students. This research uses a qualitative approach using a case study. A total of two Indonesian married female students were interviewed. The data were analyzed using thematic analysis. Then, data from the interviews were transcribed and keywords were identified. To analyze the data, the researcher also identified the themes for further exploration. The findings showed that the factors to pursue higher education could be categorized into push factors and pull factors. The results indicate that the students not only need strength of the intention, but also need to make targets and strategies during studies, as well as to build a support system with family member, relatives, and friends to complete their studies.